Short review: Application Areas of Industry 4.0 Technologies in Food Processing Sector - Noor Hasnan N.Z.; Yusoff Y.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Accident prevention; Augmented reality; Cost reduction; Digital storage; Food processing; Food safety; Industry 4.0; Internet of things; Regulatory compliance; Technology transfer; Digital technologies; Food industries; Food manufacturing; Intelligent Manufacturing; Technological advancement; Technological constraints; Technological revolution; User friendly interface; Processed foods